2010
DOI: 10.1128/jvi.00962-10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity and Sites of Recombination in Human Rhinovirus Species C

Abstract: Human rhinoviruses (HRVs) are a highly prevalent and diverse group of respiratory viruses. Although HRV-A and HRV-B are traditionally detected by virus isolation, a series of unculturable HRV variants have recently been described and assigned as a new species (HRV-C) within the picornavirus Enterovirus genus. To investigate their genetic diversity and occurrence of recombination, we have performed comprehensive phylogenetic analysis of sequences from the 5 untranslated region (5 UTR), VP4/VP2, VP1, and 3Dpol r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 60 publications
10
106
0
Order By: Relevance
“…Specifics of both HRV-C evolution and the two classification frameworks could play a role. The genetic diversity of these viruses in capsid (1A, also known as VP4, and 1D proteins) and nonstructural (3D) regions was previously reported to exceed those of other rhinoviruses (51,69). In the 1D protein, this difference is smallest, and the entire HRV-C diversity was considered to be below the species divergence limit, paving the way for the recognition of HRV-C as a single species.…”
Section: Resultsmentioning
confidence: 99%
“…Specifics of both HRV-C evolution and the two classification frameworks could play a role. The genetic diversity of these viruses in capsid (1A, also known as VP4, and 1D proteins) and nonstructural (3D) regions was previously reported to exceed those of other rhinoviruses (51,69). In the 1D protein, this difference is smallest, and the entire HRV-C diversity was considered to be below the species divergence limit, paving the way for the recognition of HRV-C as a single species.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, HRV-C strains were detected in patients with various ARIs such as URI and bronchitis. In addition, previous reports have suggested that~30 genotypes with high genetic divergence are found in various HRV-C strains (McIntyre et al, 2010;Simmonds et al, 2010). The present strains were also classified into 11 genotypes with a relatively wide divergence, although only a small number of HRV-C strains were examined in the current study.…”
Section: Discussionmentioning
confidence: 88%
“…To assign genotypes to each of the present strains, we used the 28 HRV-C reference strains (Arakawa et al, 2012;Simmonds et al, 2010). In addition, to assess interspecies frequency distributions of HRV-C, we calculated pairwise distances for all of the HRV-C strains, both present strains and reference strains, as described previously (Arakawa et al, 2012;Mizuta et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations